Means of payment and degree of monetization: A suggestion and an application to the case of Portugal - Ana Tomás; Nuno Valério (The Journal of European Economic History, 2020)
Given that the characteristics of the sets of means of payment available to economic agents at a given moment supply decisive information about the degree of monetization of the economy, this paper first proposes a technique to analyse these characteristics, considering their amplitude, purchasing power and density, and then applies that technique to the evolution of the monetary system of Portugal in the course of its existence as an independent country. The Portuguese case is an interesting standard for international comparisons, because it evolved over a very long time span, and sharply different degrees of monetization may be identified within it: (i) an epoch of low or negligible monetization (12th-15th century); (ii) monetization of a significant and gradually increasing part of the economy (15th19th century); and (iii) almost full monetization (19th century on).
Keywords: 330